FAKTOR MANUSIA DAN ERGONOMIS PENGGUNAAN KOMPUTER UNTUK MENINGKATKAN KESEHATAN DAN KESELAMATAN KERJA (K3) - Pujadi, Tri (CommIT (Communication and Information Technology) Journal, 2008)
Interaction with computer is considered with excitement because perhaps it is more efficient. But, there was an endangering aspect which also would mount which was a health work. Health problem came from the intensity of computer usage, in a low level or injury trouble which emerged for the long run after when using a computer. By evolusive, the end result became equal in the form of serious health trouble. This article can inspire to feel awareness human factor and ergonomic in use of computer, either in environment work, public place or other places and expected also can give benefit for good society in creating creative new idea and inovation to develop technology of more computer pay attention to factor of human and ergonomic.Keywords: human factors, ergonomic, computer, health and safety